Modeling and proportional integral sliding mode control of hydraulic manipulators - Azlan, N. Z.; Osman, Johari Halim Shah (2006)
This paper is concerned with the mathematical modeling and the application of a new position tracking control technique for hydraulic manipulators. The integrated model takes into account both the manipulator linkage as well as the actuator dynamics to represent a closer dynamic behaviour of the real system, thus providing a more suitable model for the purpose of advanced controller synthesis and analysis. Although hydraulic manipulators provide large torque and fast response, they possess highly nonlinear dynamics, parameter variations, uncertain load disturbances and strong couplings among various joints. Therefore, a robust control approach based on proportional integral sliding mode control (PISMC) technique is adopted to provide position tracking for the system. It will be shown that the proposed controller is practically stable and is successful in forcing the robotic system to track the predefined desired trajectory at all time. A 3 DOF revolute robot manipulator is used in this study.